Optoelectronic Inactivity of Dislocations in Cu(In, Ga)Se2 Thin Films. Issue 7 (27th May 2021) - Abou-Ras, Daniel; Nikolaeva, Aleksandra; Krause, Maximilian; Korte, Lars; Stange, Helena; Mainz, Roland; Simsek Sanli, Ekin; van Aken, Peter A.; Sugaya, Takeyoshi; Nishinaga, Jiro
Abstract : High‐efficiency Cu(In, Ga)Se2 (CIGS) thin‐film solar cells are based on polycrystalline CIGS absorber layers, which contain grain boundaries, stacking faults, and dislocations. While planar defects in CIGS layers have been investigated extensively, little is still known about the impact of dislocations on optoelectronic properties of CIGS absorbers. Herein, evidence for an optoelectronic inactivity of dislocations in these thin films is given, in contrast to the situation at grain boundaries. This unique behavior is explained by the extensive elemental redistribution detected around dislocation cores, which is connected with the dislocation strain field, probably leading to a shift of defect states toward the band edges. Abstract : Dislocations and antiphase domain boundaries in epitaxially grown Cu(In, Ga)Se2 thin films do not seem to be optoelectronically active, as evidenced by cathodoluminescence hyperspectral imaging. Thus, these extended structural defects exhibit similar recombination behaviors as the Cu(In, Ga)Se2 bulk. These findings can be explained by elemental redistribution around the dislocation core, relaxing the atomic lattice and therefore probably also the defect levels.